Colloidal synthesis of two-dimensional transition metal chalcogenide nanomaterials and their application in catalysis - Chen, Jiayi (Curtin University, 2023)
Low-dimensional nanocrystals, especially one-dimensional (1D) and two-dimensional (2D) nanostructures find wide applications in catalysis, optoelectronics, energy storage and more. The projects conducted in this thesis are mainly focusing on the synthesis and self-assembly of 2D transition metal chalcogenides and their applications towards photocatalysis and electrocatalysis, as well as the growth mechanistic study of zigzag CsPbBr3 perovskite nanocrystals.